The Comparing of Problem-Based Learning and Lecture-Based Learning on Students’ Learning Outcomes and Satisfaction for a Family Health Nursing Course - Tantut Susanto; Hanny Rasni; Latifa Aini Susumaningrum; Rismawan Adi Yunanto (Jurnal Keperawatan Padjadjaran, 2022)
Background: Problem - Based Learning (PBL) is a method of student-centered learning. In PBL, students become centered to the learning process, whereas the teacher is the center of learning in lecture-based learning (LBL). Purpose: This study aimed to compare the effects of PBL and LBL on students’ learning outcomes and satisfaction on an undergraduate nursing course. Methods: Quasi-experimental study. Participants included 161 students from two different classes of the course; in 2013, as a control group (n = 88) and in 2014 as an intervention group (n = 73). Both groups received LBL, which is practice in the lab and clinic, but the intervention group also received PBL. Secondary data analysis of students’ learning outcomes was measured using students’ learning progress in tests from lecture (theory, paper, laboratory, and clinical), while students’ satisfaction was measured using teaching method evaluation from students. Results: Students’ learning outcomes (theory, laboratory, and clinical) in the PBL group were significantly more than in the control group (p<0.001), whereas paper lesson outcomes were higher in control group compared to the intervention group (t=6.43; p<0.001; 95% CI=1.46-2.76). There was more satisfaction with the PBL method. There was no relationship between students’ satisfaction and learning outcomes (p>0.05). However, students considered greater satisfaction in PBL compared to LBL. Conclusions: In problem-based learning, students contributed a lot to solving the problem and getting the skills and knowledge they needed. Students are also expected to be motivated.